EFEKTIVITAS PENERAPAN PATHFINDER PADA LAYANAN DEPOSIT DINAS PERPUSTAKAAN PROVINSI SUMATERA SELATAN - Pratiwi, Antika (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Advances in technology in the current era of libraries are already using a computerized system or often referred to as OPAC as a means of searching for information in the library. The purpose of the pathfinder is to help users who will be looking for information on specific problems but do not understand and know the sources of information in the library. Pathfinder contains bibliographical sources related to a particular subject from books, papers, periodicals, reference sources, websites, audio visuals, and so on. Information contained in the pathfinder: pathfinder title, scope, type of information source, information source title, physical description, call number, annotation, and location. Libraries as information centers & sources knowledge that are inexhaustible to be explored, drawn, and developed, should provide optimal information retrieval facilities for the users of the library itself. This study aims to determine the utilization and use of pathfinders in the Library Service. This study uses a qualitative descriptive research method which will provide an overview to the reader about the effectiveness of implementing pathfinder.